1966
DOI: 10.3758/bf03210057
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of verbal and non-verbal reports of fragmenting visual Images

Abstract: Sixty-eight Ss voluntarily restrained head, eye and blinking movements while viewing a luminous "HB" figure in a darkened room. All Ss were told that voluntary fixation would cause parts of the pattern to disappear; they were to report the parts that remained intact. Half of the Ss reported their disappearances verbally. The other half traced their disappearances on an outline "HB" figure. Results showed that the verbal method significantly favored the reporting of elements from the set H, h, B, b, 1, 11, +. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Concurrent verbalisation is a process in which an individual verbalises cognitive processes while performing a task. This "thinking aloud" (Ericsson & Simon, 1980) has been used successfully in the study of mental processes, such as problem-solving (e.g., Newel1 & Simon, 1972), visual and verbal coding (e.g., Schuck & Leahy, 1966), cueprobability learning (e.g., Brehmer, 1974), concept learning (e.g., Bower & King, 1967), mental multiplication (e.g., Dansereau & Gregg, 1966), performance on intelligence tests (e.g., Merz, 1969), concentration during running (Schemer, 1986), and expertise in chess (DeGroot, 1965). Studies on imaginal activity in nonsporting situations have used concurrent verbalisation (e.g., Bertini, Lewis, & Witkin, 1969;Klinger, 1971;Kazdin, 1975Kazdin, , 1976Kazdin, , 1979Klos & Singer, 1981;Petre & Blackwell, 1999).…”
Section: Measurement Of Image Y Perspective Usementioning
confidence: 99%
“…Concurrent verbalisation is a process in which an individual verbalises cognitive processes while performing a task. This "thinking aloud" (Ericsson & Simon, 1980) has been used successfully in the study of mental processes, such as problem-solving (e.g., Newel1 & Simon, 1972), visual and verbal coding (e.g., Schuck & Leahy, 1966), cueprobability learning (e.g., Brehmer, 1974), concept learning (e.g., Bower & King, 1967), mental multiplication (e.g., Dansereau & Gregg, 1966), performance on intelligence tests (e.g., Merz, 1969), concentration during running (Schemer, 1986), and expertise in chess (DeGroot, 1965). Studies on imaginal activity in nonsporting situations have used concurrent verbalisation (e.g., Bertini, Lewis, & Witkin, 1969;Klinger, 1971;Kazdin, 1975Kazdin, , 1976Kazdin, , 1979Klos & Singer, 1981;Petre & Blackwell, 1999).…”
Section: Measurement Of Image Y Perspective Usementioning
confidence: 99%
“…If the S simply repeats the digits in each visual display, not only are the visual stimuli 3 and 2 (as well as 8 and 5) appearing in close temporal and spatial connection but also these verbal responses are concurrmg with equal frequency. By having the S report the total number of digits, the perceptual learning experience is restricted to S-S associations rather than to response mediated associations that have been previously demonstrated (Donderi & Kane, 1965;McKinney, 1966;Schuck & Leahy, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…The role response training plays in influencing perceptual disappearances has been questioned. Schuck and Leahy (1966) compared verbal and nonverbal reports of fragmentation and concluded that response training and bias did not affect the perception of stimuli but simply altered the reporting of their fragmentation.…”
mentioning
confidence: 99%